Stability and Seakeeping of Marine Vessels - Begovic, Ermina; Mancini, Simone (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book presents the papers accepted into the Special Issue "Stability and Seakeeping of Marine Vessels" and includes nine contributions to this Special Issue published in 2020. The overall aim of the collection is to improve knowledge about the most relevant and recent topics in ship stability and seakeeping. Specifically, the articles cover a wide range of topics and reflect the recent scientific efforts in the 2nd generation intact stability criteria evaluation and modelling of the ship dynamics assessment in intact or damaged conditions. These topics were investigated mainly through direct assessments performed both via numerical methods and tools, and experimental approaches. The book is addressed to individuals from universities, research organizations, industry, government agencies and certifying authorities, as well as designers, operators and owners who contribute to improved knowledge about "stability and seakeeping".